DIFFUSION BONDING : AN ADVANCED OF MATERIAL PROCESS - Rusnaldy, Rusnaldy (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2001)
Diffusion bonding or diffusion welding is a solid state joining process. This bonding technique is based on theatomic diffusion of elements at the joining interface. The diffusion-welding interface has same physical and mechanicalproperties as base metal. The strength of joining depends on pressure, temperature, time of contact and the cleanness ofthe interface. Diffusion bonding needs longer time than the other welding processes.